1992
DOI: 10.1093/bja/68.5.471
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Hypoxaemic and Cardiac Ischaemic Events in the Perioperative Period

Abstract: We have used continuous and concurrent monitoring of arterial oxygen saturation (SpO2) and ECG to study the relationship between hypoxaemia and silent myocardial ischaemia in the perioperative period in 11 patients with cardiovascular disease. Ischaemic and hypoxaemic events occurred in all patients. Many events were shortlived and occurred independently of each other. However, our results suggest a close correlation between the duration of hypoxaemia and myocardial ischaemia. Ischaemia is more likely to occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(51 citation statements)
references
References 8 publications
0
50
0
1
Order By: Relevance
“…Exacerbation of COPD may overtax an already diseased heart because of hypoxemia and increased work of breathing. It was reported that severe hypoxemia can worsen cardiac ischemia in patients with ischemic heart disease [21,22]. On the other hand, exacerbation of ischemic heart disease can further impair gas exchange by incrementally increasing airway resistance or reducing mixed venous oxyhemoglobin saturation.…”
Section: Discussionmentioning
confidence: 99%
“…Exacerbation of COPD may overtax an already diseased heart because of hypoxemia and increased work of breathing. It was reported that severe hypoxemia can worsen cardiac ischemia in patients with ischemic heart disease [21,22]. On the other hand, exacerbation of ischemic heart disease can further impair gas exchange by incrementally increasing airway resistance or reducing mixed venous oxyhemoglobin saturation.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal gas exchange induced during or after anaesthesia, abnormality of respiratory control mechanisms and post-operative pain are three interacting factors involved in the development of post-operative hypoxaemia. The effect can last for several days after an operation (GILL et al, 1992). Even spinally administered drugs can affect the respiratory centre, with inadequate respiratory rate and/or tidal volume and decreasing oxygen saturation SaO2, as a result (JONES et al, 1990).…”
Section: Clinical Aspectsmentioning
confidence: 99%
“…I ncreased cardiac morbidity after various surgical procedures has been found in relation to late postoperative hypoxemia, [1][2][3][4] and several studies [1][2][3][4] have described a time-related connection between late postoperative hypoxemia and myocardial ischemia after noncardiac surgery. Further, it has been shown in animal experiments that arterial hypoxemia can worsen ischemia in an already ischemic myocardium.…”
mentioning
confidence: 99%